(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the general patterns and features of speech formation and development in children with visual impairments. It also analyzes the comparison of speech development rates with peers observed in the norm, and how speech is reflected as a holistic system, rather than individual components.